COVID-19 Pandemic-Frontline Experiences and Lessons Learned From a Tertiary Care Teaching Hospital at a Suburban Location of Southeastern India - V. Nirmal Coumare; Swati Jayant Pawar; P. S. Manoharan; R. Pajanivel; Lokesh Shanmugam; Hemanth Kumar; Abhijit V. Boratne; Balanehru Subramanian; Joshy M. Easow; B. Sivaprakash; R. Kalaivani; K. Renuka; et al. (Frontiers Media S.A., 2021)
The key challenges to any health care setup during emergency situations, such as that of the COVID-19 pandemic would be to rapidly address hospital preparedness and response tailored to the local population, societal influences, political factors within the existing infrastructure, and workforce. Second, to adopt and moderate policies, standard operating procedures (SOPs) and guidelines issued by national and international agencies, such as WHO, CDC, and the Indian Council for Medical Research (ICMR) were tailor-made to the local conditions of the hospital and community. In this publication, we have discussed the challenges and experiences in preparation and responses to the ongoing COVID-19 pandemic at a tertiary teaching hospital situated at a suburban locale in a small union territory. Puducherry is located in the South Eastern Coromandel Coast of India. The core processes, such as hospital preparedness, adoption, and amendments to SOPs based on dynamic changes in guidelines released by the central and local government, training given to health care workers, setting up the in-house diagnostic facility, surge capacity, management of supplies during the lockdown, infection prevention, and control and patient care are discussed. We have also reinforced our experiences in translating COVID-related opportunities for research and innovation in the form of awards and research proposals for the faculty and students of our institute. The lessons learned in terms of strength and limitations on the ground level of public health during this process is worth sharing as it would provide guidance in preparing the health care setups for pre- and post-pandemic.